The toxicity of petroleum pollutants on marine zooplankton: Multiscale effects from individuals to populations - Tianrui Liu; Xiahui Liu; Wangguangming Yu; Jingfeng Bai; Wei Shen; Xuan Wu (Marine Pollution Bulletin, 2026)

Can digital transportation contribute to mitigating environmental pollution? Evidence from the Chinese Context - Rui Liu; Liyin Shen; Jingfeng Yuan (Journal of Cleaner Production, 2026)

Impact of age on safety of pancreaticoduodenectomy: a nationwide cohort study stratified by surgical approach and anastomotic technique with optimal age cut-off analysis - Hongwei Huang; Feng Xia; Tianyin Shao; Baiyong Shen; Xinmin Yin; Xiaoqing Jiang; Deyu Li; Jing Li; Sen Qiao; Songqing He; Heshui Wu; Jiayun Ge; et al. (Science China Life Sciences, 2026)

Causal effects of immune cell populations on biological aging: a Mendelian randomization study - Jingfeng Fu; Wei Wu; Shangren Shen (Biogerontology, 2026)

The dual role of water in CO2 capture by a novel 2-(ethylamino)ethanol-based non-aqueous phase-change absorbent: A net positive effect - Dunqiu Wang; Jingfeng Shen; Dan Wang; Yinming Fan; Shengpeng Mo; Bihong Lv; Yanan Zhang; Yinian Zhu; Zongqiang Zhu; Mi Feng; Xiaobin Zhou; Guohua Jing (Chemical Engineering Journal, 2025)

Mechanical analysis of eccentrically loaded SFRC columns reinforced by high-strength rebars: Testing and FE modelling - Ziming Hu; Jingfeng Wang; Qihan Shen; Beibei Li; Yong Liu (Engineering Structures, 2025)

Gradient multi-component interphase enabling highly reversible magnesium metal anode in fluorinated alkoxyborate-based electrolytes - Yuhang Chen; Yiming Zhang; Zhimeng Tang; Zhenyu Zhang; Le Tong; Xuemin Gan; Xing Shen; Guangsheng Huang; Qian Li; Baihua Qu; Fusheng Pan; Jingfeng Wang (Chemical Engineering Journal, 2025)

The environmental concentration of diethylstilbestrol and its structural analogues promote the conjugation transfer of ARGs through the pheromone effect - Panpan Yang; Xiaobo Yang; Feng Wang; Rumeng Li; Man Zhang; Jingxue Qian; Ruolin Hao; Zhiqiang Shen; Jingfeng Wang; Lijuan Zhang; Zhigang Qiu; Yanhua Cao (Journal of Hazardous Materials, 2025)

Elimination of representative antibiotic-resistant bacteria, antibiotic resistance genes and ciprofloxacin from water via photoactivation of periodate using FeS2 - Fuyang Liu; Yutao Shen; Yanghui Hou; Jingfeng Wu; Yong Ting; Chenyi Nie; Meiping Tong (Journal of Hazardous Materials, 2024)

A cell-free fluorescence biosensor based on allosteric transcription factor NalC for detection of pentachlorophenol - Shuting Chen; Chen Zhao; Xiaodan Kang; Xi Zhang; Bin Xue; Chenyu Li; Shang Wang; Xiaobo Yang; Chao Li; Zhigang Qiu; Jingfeng Wang; Zhiqiang Shen (Biotechnology Letters, 2024)

Chlorite and bromate alter the conjugative transfer of antibiotic resistance genes: Co-regulation of oxidative stress and energy supply - Jinrui Cao; Bin Xue; Shuran Yang; Xiaobo Yang; Xi Zhang; Zhigang Qiu; Zhiqiang Shen; Jingfeng Wang (Journal of Hazardous Materials, 2024)

Environmental concentrations of acetaminophen and its metabolites promote the spread of antibiotic resistance genes through pheromone signaling pathway - Xinyue Fu; Xiaobo Yang; Xiaoli Lin; Li Zhu; Panpan Yang; Feng Wang; Zhiqiang Shen; Jingfeng Wang; Yun Ling; Zhigang Qiu (Chemical Engineering Journal, 2024)

Metabolic shifts in glycogen-accumulating organisms: Exploring carbon and phosphorus dynamics under two distinct phosphorus limitation modes - Shang Wang; Chenyu Li; Chunchun Zhang; Yuchao Liu; Sheng Li; Yiqiu Fang; Zhiqiang Shen; Jingfeng Wang (Journal of Cleaner Production, 2024)

Multidrug-resistant plasmid RP4 inhibits the nitrogen removal capacity of ammonia-oxidizing archaea, ammonia-oxidizing bacteria, and comammox in activated sludge - Zhaohui Zhang; Lin Bo; Shang Wang; Chenyu Li; Xi Zhang; Bin Xue; Xiaobo Yang; Xinxin He; Zhiqiang Shen; Zhigang Qiu; Chen Zhao; Jingfeng Wang (Environmental Research, 2024)

The occurrence, ecological risk, and control of disinfection by-products from intensified wastewater disinfection during the COVID-19 pandemic - Bin Xue; Xuan Guo; Jinrui Cao; Shuran Yang; Zhigang Qiu; Jingfeng Wang; Zhiqiang Shen (Science of The Total Environment, 2023)

Graphite carbon nitride photocatalytic materials: A roadmap to modification for current and future water purification - Xinyuan Zhang; Chenyu Li; Lin Dai; Chuanling Si; Zhiqiang Shen; Zhigang Qiu; Jingfeng Wang (Journal of Environmental Chemical Engineering, 2023)

Multidrug-resistant plasmid RP4 increases NO and N2O yields via the electron transport system in Nitrosomonas europaea ammonia oxidation - Jia Li; Chen Zhao; Chenyu Li; Bin Xue; Shang Wang; Xi Zhang; Xiaobo Yang; Zhiqiang Shen; Lin Bo; Xinxin He; Zhigang Qiu; Jingfeng Wang (Water Research, 2023)

Pheromone effect of estradiol regulates the conjugative transfer of pCF10 carrying antibiotic resistance genes - Xiaobo Yang; Yuanyuan Niu; Yutong Yang; Hongrui Zhou; Jing Li; Xinyue Fu; Zhiqiang Shen; Jingfeng Wang; Zhigang Qiu (Journal of Hazardous Materials, 2023)

Docosahexaenoic acid inhibits pheromone-responsive-plasmid-mediated conjugative transfer of antibiotic resistance genes in Enterococcus faecalis - Hongrui Zhou; Xiaobo Yang; Yutong Yang; Yuanyuan Niu; Jing Li; Xinyue Fu; Shang Wang; Bin Xue; Chenyu Li; Chen Zhao; Xi Zhang; Zhiqiang Shen; et al. (Journal of Hazardous Materials, 2023)

Monitoring and evaluation of antibiotic resistance genes in three rivers in northeast China - Chen Zhao; Chenyu Li; Xiaoming Wang; Zhuosong Cao; Chao Gao; Sicong Su; Bin Xue; Shang Wang; Zhigang Qiu; Jingfeng Wang; Zhiqiang Shen (Environmental Science and Pollution Research, 2022)

Characterization of a novel Vibrio parahaemolyticus host-phage pair and antibacterial effect against the host - Chao Gao; Xiaobo Yang; Chen Zhao; Chenyu Li; Shang Wang; Xi Zhang; Bin Xue; Zhuosong Cao; Hongrui Zhou; Yutong Yang; Zhiqiang Shen; Pingfeng Yu; et al. (Archives of Virology, 2022)

An amino acid duplication/insertion in the Bm126 gene of Bombyx mori nucleopolyhedrovirus alters viral gene expression as shown by differential gene expression analysis - Jinshan Huang; Jingfeng Li; Chen Cheng; Xudong Tang; Xingjia Shen; Bifang Hao (Archives of Virology, 2019)

Aquatic animals promote antibiotic resistance gene dissemination in water via conjugation: Role of different regions within the zebra fish intestinal tract, and impact on fish intestinal microbiota - Jialun Fu; Dong Yang; Min Jin; Weili Liu; Xin Zhao; Chenyu Li; Tianyu Zhao; Jingfeng Wang; Zhixian Gao; Zhiqiang Shen; Zhigang Qiu; Jun‐Wen Li (Molecular Ecology, 2017)
The aqueous environment is one of many reservoirs of antibiotic resistance genes ( ARG s). Fish, as important aquatic animals which possess ideal intestinal niches for bacteria to grow and multiply, may ingest antibiotic resistance bacteria from aqueous environment. The fish gut would be a suitable environment for conjugal gene transfer including those encoding antibiotic resistance. However, little is known in relation to the impact of ingested ARG s or antibiotic resistance bacteria ( ARB ) on gut microbiota. Here, we applied the cultivation method, qPCR , nuclear molecular genetic marker and 16S rDNA amplicon sequencing technologies to develop a plasmid‐mediated ARG transfer model of zebrafish. Furthermore, we aimed to investigate the dissemination of ARG s in microbial communities of zebrafish guts after donors carrying self‐transferring plasmids that encode ARG s were introduced in aquaria. On average, 15% of faecal bacteria obtained ARG s through RP 4‐mediated conjugal transfer. The hindgut was the most important intestinal region supporting ARG dissemination, with concentrations of donor and transconjugant cells almost 25 times higher than those of other intestinal segments. Furthermore, in the hindgut where conjugal transfer occurred most actively, there was remarkable upregulation of the mRNA expression of the RP 4 plasmid regulatory genes, trbBp and trfAp . Exogenous bacteria seem to alter bacterial communities by increasing Escherichia and Bacteroides species, while decreasing Aeromonas compared with control groups. We identified the composition of transconjugants and abundance of both cultivable and uncultivable bacteria (the latter accounted for 90.4%–97.2% of total transconjugants). Our study suggests that aquatic animal guts contribute to the spread of ARG s in water environments.

Etiology and epidemiology of viral diarrhea in children under the age of five hospitalized in Tianjin, China - Yabo Ouyang; Hui Ma; Min Jin; Xinwei Wang; Jingfeng Wang; Lu Xu; Shuxiang Lin; Zhiqiang Shen; Zhaoli Chen; Zhigang Qiu; Zhixian Gao; Lin Peng; et al. (Archives of Virology, 2012)